Rates Of Adsorption Of Co2 On Hydrotalcite - Isa, Nadia (2011)
Hydrotalcite has recently attracted the attention in CO2 removal technology because of its ability to adsorb appreciable amounts of CO2 compared with many others adsorbents. Many studies have been carried out in order to investigate the structure and equilibrium adsorption capacities of CO2 hydrotalcite with different temperatures. However, studies on the rates of adsorption of CO2, which is an important aspect in the determination of the viability of the removal of CO2 have not been addressed so far. Hence it has become necessary to study the rates of adsorption of CO2 on hydrotalcite. Even though hydrotalcite powders have shown excellent potential for removal of CO2, complexities of handling hydrotalcite powders in commercial scale can be expected. This could be overcome by the use of pellets of hydrotalcite as an alternative to powders. Therefore, this study is aimed for studying the rates of adsorption of CO2 on hydrotalcite powders as well as pellets. Experiments were conducted to determine the adsorption rates of CO2 on commercial hydrotalcite powder and pellets of three different diameters (8mm, 15mm and 20mm) at the temperatures of 32oC, 300oC and 550oC respectively. Experiments were also conducted to determine the rates of adsorption of CO2 on pellets coated with hydrotalcite membrane prepared by sol gel method. Single and double coatings on pellets by dip-coating method were examined. The experiments for pellets were conducted based on Design of Experiments (DoE).Several conventional theoretical models were examined in order to investigate the kinetics of adsorption of CO2 onto hydrotalcite. The experimental data were not compatible with the conventional models. Based on the studies of Scanning Electron Microscope (SEM) analysis, Thermo Gravimetric analysis (TGA) and X-ray Diffraction (XRD) analysis, a model incorporating surface modifications of hydrotalcite with progressive adsorption of CO2 was formulated and examined for fit with experimental data. The model parameters were statistically analysed. The experimental data was observed to fit the model of surface modifications of hydrotalcite satisfactorily with correlation coefficients ranging from 0.904 to 0.923 for hydrotalcite powder and 0.827 to 0.961 for hydrotalcite pellets